Let $A$ be a $3\times3$ matrix and for any $i,j\subseteq\{1,2,3\}$, let $A^{i,j}$ denote the $2\times2$ matrix resulting from removing row $i$ and column $j$ from $A$. Then:

$\det\left(\begin{array}{ccc}\det(A^{1,1})&\det(A^{1,2})&\det(A^{1,3})\\ \det(A^{2,1})&\det(A^{2,2})&\det(A^{2,3})\\ \det(A^{3,1})&\det(A^{3,2})&\det(A^{3,3})\end{array}\right)=\det(A)^2$

  • 3
    $\begingroup$ This is actually exactly the same question as this one (which was asked yesterday!), although it is not obvious, because of different notation. $\endgroup$ – Hans Lundmark Oct 27 '11 at 6:12
  • $\begingroup$ Here is a 2007 reference about a generalization (there are hopefully earlier ones): tandfonline.com/doi/abs/10.1080/… $\endgroup$ – Jean Marie Jul 17 '20 at 14:23

Let $A$ be an $n \times n$ matrix. Let $C_{ij}$ be the $ij^{th}$ cofactor of $A$, defined by $C_{ij} = (-1)^{i+j} \det A^{ij}$ and let $$ C = \begin{bmatrix} C_{11} & C_{12} & \cdots & C_{1n} \\ C_{21} & C_{22} & \cdots & C_{2n} \\ \vdots & \vdots & \ddots & \vdots \\ C_{n1} & C_{n2} & \cdots & C_{nn} \end{bmatrix} $$ be the cofactor matrix. Also let $M$ be the matrix of minors; that is, the matrix that appears in the left hand side of the equation in the question. We will show that

  1. $\det C = (\det A)^{n-1}$, and
  2. $\det M = \det C$,

which together establish the claim.

Claim 1. From this wikipedia page, we know that $$ C^T A = A C^T = (\det A) I_n. $$

If $A$ is invertible, then taking determinants on both sides, we get: $$ \det (C^T) \cdot \det A = (\det A)^n \cdot 1. $$ Since $\det (C^T) = \det C$ and $\det A \neq 0$, we get $\det C = (\det A)^{n-1}$, and we are done.

On the other hand, if $A$ is noninvertible, then $\det A = 0$ and $ C^T A = AC^T = 0$. In this case, (WLOG assuming $n \geq 1$) it suffices to show that $\det C = 0$, which is equivalent to showing that $C$ is noninvertible as well. Here, we have two subcases:

  • If $A$ is the zero matrix, then $C$ is also the zero matrix, and hence non-invertible.

  • Suppose $A$ is nonzero. Then if $C$ is invertible, then $C^T A = 0$ implies that $$A = \Big((C^{-1})^T C^T \Big) A = (C^{-1})^T \cdot 0 = 0 ,$$ which is a contradiction. Hence $C$ is noninvertible, and we are done.

Claim 2. We now prove that $\det M = \det C$. We have the relation $C_{ij} = (-1)^{i+j} M_{ij} = (-1)^{i+j} \det A^{ij}$. So, if we take the matrix $M$, and multiply the $i^{\rm th}$ row by $(-1)^i$ and $j^{\rm th}$ column by $(-1)^j$, then we end up with the matrix $C$. In this process, the determinant gets multiplied by $$ \left(\prod_{i=1}^n (-1)^i \right) \left(\prod_{j=1}^n (-1)^j \right) = \left(\prod_{i=1}^n (-1)^i \right)^2 = \prod_{i=1}^n (-1)^{2i} = 1. $$ In other words, $\det C = \det M$.

  • $\begingroup$ What if $\det(A)=0$? The formula still works, but the proof it doesn't... Anyhow, $AC=\det(A)I$ proves it amediatelly in this case too. $\endgroup$ – N. S. Oct 26 '11 at 22:24
  • $\begingroup$ I think you're forgetting a transpose. $\endgroup$ – Grasshopper Oct 26 '11 at 22:25
  • 1
    $\begingroup$ Magic trick when $\det A = 0$: Suppose entries of the matrix are $a_1, a_2, \dots, a_n$. Consider matrix from $R[x_1, x_2, \dots, x_n]$ where $a_i$ is replaced by new variable $x_i$ from polynomial ring. Now $\det A$ is a nonzero polynomial. Proceed with proof and then use evaluation homomorphism in final equality. Doesn't need continuity. $\endgroup$ – sdcvvc Oct 26 '11 at 22:30
  • $\begingroup$ @Srivatsan Narayanan: If $\det(A)=0$ then $AC=0_n$. Then $C$ cannot be invertible cause then $A=0$ which would make $C=0$ ;) $\endgroup$ – N. S. Oct 26 '11 at 22:30
  • $\begingroup$ @user9176 Thanks for the comment. I rewrote the answer completely incorporating it. $\endgroup$ – Srivatsan Oct 27 '11 at 0:28

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.